AUTECOLOGY AND CONSERVATION BIOLOGY OF CENTAUREA AMAENA (ASTERACEAE) - Bayram Atasagun; Ahmet Aksoy (Journal of Animal and Plant Sciences, 2018)
Centaurea amaena is an endemic plant species that is under critical risk of extinction and was known from only one population in Kayseri, Turkey. During our research another locality was found at about 15 km distance from the first known population. In this study, the population pattern of this species and its distribution, the reasons for its narrow range, its pollen viability, stigma receptivity, and the breeding system have been identified, and practical efforts have been carried out for conservation. Pollination experiments showed that C. amaena pollination mechanism allows first for allogamy and then secondary pollen presentation and that the timing pollen viability and stigma receptivity are asynchronous. The seed-to-ovule ratio was calculated as 35%.  According the tetrazolium staining viability test, the seed viability also was determined as 82.6%. The main factor threatening the species were identified to be anthropogenic-related (including construction, over-grazing, tourism), and some strategies have been developed for the purpose of conservation it.
Keywords: Centaurea amaena is an endemic plant species that is under critical risk of extinction and was known from only one population in Kayseri; Turkey. During our research another locality was found at about 15 km distance from the first known population. In this study; the population pattern of this species and its distribution; the reasons for its narrow range; its pollen viability; stigma receptivity; and the breeding system have been identified; and practical efforts have been carried out for conservation. Pollination experiments showed that C. amaena pollination mechanism allows first for allogamy and then secondary pollen presentation and that the timing pollen viability and stigma receptivity are asynchronous. The seed-to-ovule ratio was calculated as 35%. According the tetrazolium staining viability test; the seed viability also was determined as 82.6%. The main factor threatening the species were identified to be anthropogenic-related (including construction; over-grazing; tourism); and some strategies have been developed for the purpose of conservation it.